(untitled) (IUPHAR/BPS Guide to Pharmacology CITE, 2019)
Vasopressin (AVP) and oxytocin (OT) receptors (nomenclature as recommended by NC-IUPHAR [92]) are activated by the endogenous cyclic nonapeptides vasopressin and oxytocin. These peptides are derived from precursors which also produce neurophysins (neurophysin I for oxytocin; neurophysin II for vasopressin). Vasopressin and oxytocin differ at only 2 amino acids (positions 3 and 8). There are metabolites of these neuropeptides that may be biologically active [67].